Assessing habitat quality in relation to the spatial distribution of protected areas in Italy. (1st October 2017) - Sallustio, Lorenzo; De Toni, Andrea; Strollo, Andrea; Di Febbraro, Mirko; Gissi, Elena; Casella, Laura; Geneletti, Davide; Munafò, Michele; Vizzarri, Matteo; Marchetti, Marco
Abstract: The conservation of species and habitats is increasingly threatened by anthropogenic impacts, particularly land use change, from local to global scales. Although many efforts have been carried out so far to halt or at least reduce the biodiversity loss (e.g., the establishment of protected areas' networks), there are still both knowledge and policy gaps slowing the conservation of species and habitats in complex environments, such as the Mediterranean region. In particular, the human-driven impacts and threats on biodiversity need more careful analysis. Accordingly, this paper aims to assess the habitat quality and degradation in Italy in relation with the spatial pattern of the current protected areas' network, mainly to identify priority areas of intervention, thus supporting large-scale conservation strategies. A survey of experts was conducted to identify the main threats for biodiversity from different land uses at the national scale. The InVEST software was then applied to assess and map habitat quality and degradation with a high spatial resolution (20 m). The relationship between habitat quality and degradation as well as their hotspots, and alternative PA categories were also explored. Results indicate that: (i) habitat quality and degradation depend on the location and intensity of the anthropogenic impacts and are sensitive to different protection levels; (ii) the combination of the survey of experts and the spatially-explicit assessment of habitat quality and degradation is useful to highlight variations of the current conditions of biodiversity and habitats; and (iii) the identification of hotspots allows one to identify priority areas for conservation. Accordingly, the proposed approach may be used to strengthen the conservation efforts in similar contexts, and thus support the implementation of the biodiversity-related policies over the long term. Highlights: We mapped habitat quality and degradation in Italy using the InVEST software. Habitat quality and degradation are linked to the protection level. Habitat quality increases where the level of protection is higher. The integration of experts' survey and mapping supports conservation efforts.